Laser treatment for stretch marks: a literature review - André Coelho Nepomuceno; Larissa Cassemiro da-Silva (Revista Brasileira de Cirurgia Plástica)
Stretch marks are scars on the dermis that cause patients to be self-conscious and that pose challenges in clinical treatment. They result from rapid stretching of the skin and often observed in adolescents, pregnant women, obese individuals, and people experiencing rapid change in weight. They initially appear as erythematous and edematous plaques (red striae), and as they mature, they become whitish and atrophic (striae alba) due to the degradation and reorganization of elastin and collagen fibers. Currently, laser treatment is an emerging noninvasive therapeutic modality that is successful in reducing the excessive vascularization of red striae and in stimulating the production of collagen and elastin in the alba. In the present literature review, PubMed was searched for articles on the treatment of atrophic striations with laser that were published from January 2000 to December 2016. The authors have found 28 articles that met the inclusion criteria. Only few randomized clinical trials have evaluated the long-term efficacy and safety of energybased treatments. Based on clinical cases and systematic reviews, both ablative and non-ablative fractional lasers caused moderate improvement in the appearance of distending striae. The 1540-nm non-ablative fractional laser is more likely to be considered the first-line treatment for stretch marks. However, future studies should focus on research with longer duration, studies with objective and standardized measures for the evaluation of results, such as biopsy results, and molecular studies showing an increase in elastic and collagen fibers that correlate to the improvement in the clinical appearance of the striae after using lasers with systematized parameters.